ANALISIS PENGARUH FASILITAS, HARGA, KUALITAS PELAYANAN DAN KERAGAMAN MENU TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Marinda Marantina, Rahayu Triastity & Suprihatmi Sri Wardiningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study to determine the significance of the effect of facility,price, service quality, and diversity of menu to customer purchase decision. Thisresearch uses a survey method which at Coffee Land Cafe & Resto in Karanganyar.Sources of data in the form of primary data and secondary data. Data collectiontechniques with questionnaires, interviews, and lilerature. The sampling technique usesaccidental sampling of 100 respondents. Data were analyzed using multiply linearregression, t test, F test, and coefficient of determination. The results of this studyindicate that the facility significantly influence consumer purchase decision at CoffeeLand Cafe & Resto in Karanganyar, prices significantly influence consumer purchasedecision at Coffee Land Cafe & Resto in Karanganyar, service qualily significantlyinfluence consumer purchase decision at Coffee Land Cafe & Resto in Karanganyar,diversity of menu significantly influence consumer purchase decision at Coffee LandCafe & Resto in Karanganyar. Four variables contributed 20,5 percent.Keywords: facility, price, service quality, menu diversity, purchase decision